PENINGKATAN KEMAMPUAN BERHITUNG MENGGUNAKAN PEMBELAJARAN KOOPERATIF BERBANTUAN MEDIA PERMAINAN ULAR TANGGA DI KB AN NAWAWI BONDOWOSO - Zaenol Fajri; Nurul Mutmainah; Sajuri Sajuri (Raudhah - Proud To Be Professional, 2023)
Early childhood grows and develops so quickly that there is a chance for them to become more competent in their early years. Giving children knowledge and developing their numeracy abilities is one of the learning tasks in early childhood education. It is the responsibility of the teacher to design learning activities for the development of numeracy abilities following the child's developmental stage, contextual factors, and standards for the accomplishment level of early childhood symbolic development. With the aid of learning resources that take the form of tangible things, like games of snakes and ladders, teachers can assist young children in developing their numeracy skills. The game of snakes and ladders is played by many players/teams, which helps develop children's social and emotional abilities and facilitates peer interaction. This study aimed to enhance students' numeracy abilities at KB An Nawawi Bondowoso through cooperative learning supported by snakes and ladders gaming media. This study is an example of classroom action research, and it has three stages: planning, action and observation, and activity reflection. The tools employed were observation logs, interviews, and documentation. According to studies, indicators were able to develop as planned and exceptionally well in each of the first two cycles, going from 69% to 77% to 86% in the third cycle. Therefore, KB An Nawawi Bondowoso's numeracy skills can be improved by using cooperative learning with the help of snakes and ladders gaming media.